Capitalism, light pollution and sleep denial: A relevant debate to the field of Collective Health (Research, Society and Development, 2021)
Objective: This article intends to raise the discussion of biological, cultural and socioeconomic aspects related to light pollution and sleep denial. Methodology: This is an essay, in which the themes are approached with the field of Collective Health, considering the scarcity of studies in the literature on this perspective, and the area's commitment to the discussion of these productive, social and cultural configurations that influence the health and quality of life of the subjects. Results and Discussion: The flexibility and instability of the labor market, in addition to the large amount of information and products to be consumed, make the day insufficient and the night is now used for carrying out various activities to the detriment of sleep. Thus, a compulsory character of adherence to the ways of living influenced by the 24/7 model stands out and the consequences of this structure for the health of individuals and populations, while the influence of the same capitalist system for the commodification of health, which feeds back into the operating system. Conclusion: The effects of the current mode of production and the impacts on the well-being of individuals and populations make this a key discussion for the field of Public Health, which can contribute to the understanding of a quality of life beyond the productivist/consumerist perspectives.